Evaluación de los mediadores IL-1α, IL-1β y TNF-α, en fluido gingival crevicular de pacientes con periodontitis - Simone, Rosamary (2019)
Objective. Evaluate the levels of inflammatory chemical mediators such as interleukin- 1α(IL-1α), interleukin-1β (IL-1β), tumorosis factor-α (TNF-α) and clinical parameters in patients diagnosed with chronic or aggressive periodontitis, before and after non-surgical periodontal therapy (NSPT). Methods. Crevicular gingival fluid (CGF) samples were taken in 11 patients diagnosed with periodontitis and 11healthy controls for evaluating levels of IL-1α, IL-1β, TNF-α before and after the NSPT, using the ELISA technique (Immunosorbent Assay Linked to enzymes). Results. In the group with periodontitis the decrease of the clinical parameters after the treatment is also observed (p <0.05). In FGC, IL-1β had the highest levels, followed by IL-1α and TNF-α. After NSPT, IL-1β decreased 17 times its concentration and IL-1α 4 times in relation to the initial values, however, only a statistically significant relationship for TNF-α. The major relationships with the clinical parameters of periodontal disease were observed for IL-1β(p<0.01), followed by IL-1α (p<0.05) and a low correlation with TNF-α. Conclusions. In this study, the group of patients with periodontitis presented higher levels of IL-1α, IL-1β and TNF-α in FGC, with IL-1β being the highest cytokine. After NSPT, periodontal clinical values have been significantly reduced. Likewise, the interleukins reduced their average values, without reaching the control of the group. The correlations observed between periodontal indices and mediators are mostly related to IL-1β with the clinical signs of periodontal disease.